THE ROLE OF COURTS IN RESOLVING CASES OF BANKRUPTCY OF ISLAMIC BANK CUSTOMERS - Sri Wahyuni; Fahmi, Chairul; Sholihin, Riadhus; Rasyid, Laila Muhammad (JURISTA: Jurnal Hukum dan Keadilan, 2023)
This paper aims to analyses the dualism of authority in resolving disputes over bankruptcy cases in Islamic banking. On the one hand, the authority is given to the judiciary of the commercial court, on the other hand, there are rules that the settlement of economic disputes in Islamic banking is resolved by the religious court. This research was conducted with a normative legal approach, where the main data was obtained from the study of legislation, doctrine and legal theories on the authority of the court, as well as secondary data from studies conducted by previous researchers related to the topic of this article. The results show that the authority to resolve disputes over bankruptcy cases of Islamic banking customers is the authority of the Religious Court as stipulated in the Religious Court Law. However, the KPKPU Act also states that the authority is also given to the Commercial Court. Judging from the theory of authority, the dualism of these rules creates legal uncertainty because the KPKPU Law and the PA Law vest the authority to resolve bankruptcy disputes in two different judicial bodies. The provisions of the KPKPU Law and the PA Law are incoherent and incompatible with each other, resulting in legal uncertainty in the resolution of commercial disputes in Islamic banking in Indonesia.